2021
DOI: 10.3390/geotechnics1010004
|View full text |Cite
|
Sign up to set email alerts
|

Review of Recent Developments and Understanding of Atterberg Limits Determinations

Abstract: Among the most commonly specified tests in the geotechnical engineering industry, the liquid limit and plastic limit tests are principally used for (i) deducing useful design parameter values from existing correlations with these consistency limits and (ii) for classifying fine-grained soils, typically employing the Casagrande-style plasticity chart. This updated state-of-the-art review paper gives a comprehensive presentation of salient latest research and understanding of soil consistency limits determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 74 publications
(184 reference statements)
0
4
0
Order By: Relevance
“…Another promising mechanism was that, during the soil preparations under the controlled-moisture conditions (22%, OMC of NS), moisture used in this study should show a wider gap between PL with increasing nZVI effects. The larger gap was from 7.3 to 29.2 with nZVI from 0.2% to 5%, even with larger PI (usually related to the specific strength), which could suggest that the water content and its position in Atterberg limits should be considered as potential factors in the damping ratio and dynamic response with nZVI treatment [58].…”
Section: Damping Ratio Characteristicsmentioning
confidence: 99%
“…Another promising mechanism was that, during the soil preparations under the controlled-moisture conditions (22%, OMC of NS), moisture used in this study should show a wider gap between PL with increasing nZVI effects. The larger gap was from 7.3 to 29.2 with nZVI from 0.2% to 5%, even with larger PI (usually related to the specific strength), which could suggest that the water content and its position in Atterberg limits should be considered as potential factors in the damping ratio and dynamic response with nZVI treatment [58].…”
Section: Damping Ratio Characteristicsmentioning
confidence: 99%
“…Additionally, a separate study highlighted the capacity of clay to expand as a result of fluctuations in water content, which can be induced by groundwater, leading to upward pressure on foundations. The expansion of clay and the resulting swelling pressure can result in substantial damage, including the cracking of walls, beams, and columns, particularly when the soil's swelling pressure exceeds the foundation load [17,18,19].…”
Section: Despitementioning
confidence: 99%
“…Meanwhile, the inclusion of hygroscopic water content [27] provided another unique pathway, and this is an indication that the conventional liquid limit and plastic limit determination could be replaced by investigating soil-water interactions further in a systematic fashion. A review of the recent trend by O'Kelly [28] suggested that an alternative method to determine the Atterberg limit remains a topic of paramount importance.…”
Section: Introductionmentioning
confidence: 99%